A DRIVER's guide to European repositories - Weenink, Kasja; Waaijers, Leonardus Johannes Maria, 1938-; Godtsenhoven, Karen van (Surf / EU-Driver., 2008)
The Driver's Guide is a practical guide for repository managers and institutions who want to build their own repository.